Modification of the existing maximum residue level for cyprodinil in rhubarbs. (13th September 2019) - ,; Anastassiadou, Maria; Brancato, Alba; Carrasco Cabrera, Luis; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; Nave, Stefanie; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the Agriculture and Horticulture Development Board (AHDB) in the United Kingdom submitted a request to the competent national authority to modify the existing maximum residue level (MRL) for the active substance cyprodinil in rhubarbs. The data submitted in support of the request were found to be sufficient to derive an MRL proposal of 2 mg/kg for rhubarbs. Adequate analytical methods for enforcement are available to control the residues of cyprodinil in the plant matrix under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of cyprodinil according to the reported agricultural practice is unlikely to present a risk to consumer health.